Predicting basal insulin rates on insulin pumps in Indian patients with type 1 diabetes: The rule of 5 - Krishnan Swaminathan (Apollo Medicine)
Aims: To guide diabetes practitioners on setting up of basal rates in patients initiated on continuous subcutaneous insulin pump therapy (CSII) in India. Methods: Fifty patients on CSII for more than six months duration and stable glycemic control were analysed for mean basal rates. Results: Five basal rates per day with a thumb rule of 55% basal and 45 % bolus seems a good starting point for patients initiated on CSII therapy in the sub-continent. Conclusions: Our pilot study should guide medical professionals in setting up basal rates during CSII initiation to optimise glycemic control efficiently.